Empowering the Cipondok Village Community through sericulture cultivation and digital-based silk fabric weaving - Dhimas Suhtan Putra Nadiwa; Fadillah Al-Qorin; Nadia Aretha (University of Merdeka Malang, 2024)
Empowering the community of Cipondok Village through a digital-based sericulture and silk weaving program is a strategic effort to optimize the local economic and cultural potential. This community engagement involves members of the Community Youth Development or Karang Taruna, the Family Welfare Program or Program Kesejahteraan Keluarga (PKK), and the Sabilulungan III Factory as the target groups. The IDEAS team designed several programs to advance Cipondok Village businesses through several stages, namely the planning stage, preparation, program implementation, and monitoring evaluation. Through training and workshops, community participation has increased, leading to a significant improvement in their understanding and skills. The digital marketing program has also been successfully implemented by inaugurating the Sutra Studio Cipondok and the official village website. This new institution, along with the re-branding of woven fabric products, is expected to strengthen the sustainability of the program. The outcomes include an increase in the income of business groups, the effective implementation of marketing strategies through social media and the website, and the establishment of the Sutra Studio Cipondok institution. These steps not only support local economic growth but also integrate the silk fabric products of Cipondok Village into a broader market. The program contributes to the achievement of Sustainable Development Goals (SDGs) numbers 8 and 9 by enhancing decent work and economic growth, as well as advancing infrastructure, industry, and innovation.